The Story of Prophet Hud - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
This delightful board book is a perfect gift for little children. The Quran story of Prophet Hud and the great builders of Ad, comes with engaging illustrations, simple text and a moral in the end of the story.
Keywords: Islamic Books